2019
DOI: 10.1080/23322039.2019.1582317
|View full text |Cite
|
Sign up to set email alerts
|

Long-term interest rate predictability: Exploring the usefulness of survey forecasts of growth and inflation

Abstract: This study focuses on the consensus forecasts from the Survey of Professional Forecasters (SPF) for 1993-2017. These include the SPF forecasts of US 10-year Treasury rate (TBR), Moody's Aaa corporate bond rate (Aaa), CPI inflation, and real GDP growth. We show that both SPF and random walk forecasts of TBR and Aaa generally fail to be orthogonal to changes in SPF inflation (but not growth) forecasts. Such findings point to the potential usefulness of SPF inflation forecasts in improving the accuracy of SPF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Our empirical findings are generally consistent with existing empirical literature regarding short-term rates predictability (Chun 2012) but differ from existing evidence on long-term interest rates (Filiz et al , 2019) as we show that survey-based forecasts are also efficient in predicting long-term interest rates in the long run. Third, regarding the other key macroeconomic variables under examination, we provide evidence that survey-based forecasts are among the most accurate predictors of key macroeconomic variables, in line with the existing literature (Baghestani, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our empirical findings are generally consistent with existing empirical literature regarding short-term rates predictability (Chun 2012) but differ from existing evidence on long-term interest rates (Filiz et al , 2019) as we show that survey-based forecasts are also efficient in predicting long-term interest rates in the long run. Third, regarding the other key macroeconomic variables under examination, we provide evidence that survey-based forecasts are among the most accurate predictors of key macroeconomic variables, in line with the existing literature (Baghestani, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Long-term interest rate, in theory, follow a near random walk and thus, its best forecast is a naive estimated based on the most recent rate known at the time of the forecast (Pesando, 1979). Consistent with the theory, existing empirical evidence on the accuracy of survey forecasts of long-term interest rates have shown that such forecasts fail to beat the random walk benchmark (Baghestani, 2006, 2009a, 2018, 2019; Baghestani et al , 2015; Cho, 1996; Greer, 1999, 2003; Kolb and Stekler, 1996; Mitchell and Pearce, 2007; Stark, 2010). As for survey forecasts of short-term interest rates, existing findings are mixed (Altavilla and Giannone, 2017; Baghestani, 2010; Baghestani et al , 2015; Chun, 2012) as empirical evidence generally suggests that survey participants perform the best for short-horizon forecasts of short to medium term yields.…”
Section: Literature Reviewmentioning
confidence: 61%
See 1 more Smart Citation
“…Diebold and Lopez (), among others, note that a random walk forecast is not necessarily a naïve forecast for many economic and financial indicators. This is especially so for both exchange rates (Baghestani ; Rossi ) and long‐term interest rates (Baghestani ; ).…”
mentioning
confidence: 99%